Using photograph to improve students’ writing skill in descriptive text at seventh grade junior high school - Annisa Ilma Savitri; Endang Komariah; Fajar Riyantika (U-Jet Unila Journal of English Language Teaching, 2025)
Writing appears to be a productive English talent that most Indonesian students still struggle with, despite being one of the skills that must be mastered. This research aimed to investigate the students’ writing skill in descriptive text and to find out which aspects of writing improve the most after the students received the treatments by using the media of photograph. The sample in this study was class 7.2, which consists of 30 students of SMPN 1 Pringsewu in the academic year 2024/2025. The researcher used quantitative approach with pretest-posttest design that implemented writing test as instrument. The collected data were analyzed by using Social Science Statistical Package for Social Sciences’s Wilcoxon Test. The result showed significant improvement in students’ writing after the implementation of using photograph with a significant value of 0.000, which is lower than 0.05. Therefore, it can be concluded that the H1 is accepted, while H0 is rejected. This means that students’writing skill in descriptive text significantly improved by using photograph. The mean of students’ scores also improved from 59 in the pretest to 74 in the posttest with the gain of 15. In addition, the aspects of writing that improved the most in this study is content with the N-Gain of 45,71%.